Genetic and Non-Genetic Factors on Productive and Reproductive Performance of Indigenous Buffalo - Paneru, Uddhav; Dhungana, Keshav Prasad; Kanu, Surendra; Sharma, Parbati (Journal of Nepal Agricultural Research Council, 2021)
Indigenous buffalo is the black gold of Nepal because of its important contribution to the livelihood of the rural farmers and agricultural economy of the country. A study was done to investigate the performance of indigenous buffalo found in high-hill of the western districts of Nepal. Further, effect of genetic and non-genetic factors on productive and reproductive performance of indigenous buffalo was accessed. This study was done in four districts: Myagdi, Baglung, Parbat and Kaski for 2 consecutive years from 2016 to 2017. A semi-structured and questionnaire survey format was prepared and was filled with verbal answers from 142 farmers on a different aspect of buffalo farming. Further, recording formats were distributed to enumerators for the recording of different information that cannot be collected from the survey. Total of 201 indigenous buffaloes (132 Lime and 69 Parkote) and minimum of 25 buffaloes in each site were measured for determining productive and reproductive performance. Further, 65 collected milk samples were subjected to Animal Nutrition Laboratory of DoAR, Lumle for determination of milk composition. Results of the findings revealed that there was a high variation in productive and reproductive performance of indigenous buffalo. Lactation milk yield of Lime buffalo was observed slightly higher (1180.90 ± 27.94 L) than Parkote buffalo (1170.56 ± 42.29 L) but was non-significant (p>0.05). Lactation yield of indigenous buffalo in Ramja, Parbat (1254.73±38.43 L) was observed significantly higher (P<0.002) than other research locations. Genetic evaluation of indigenous buffaloes and selection of better performers help in increasing productivity and lead to conservation by competitive advantage of indigenous buffaloes. Non-genetic factors play an important role in the productive and reproductive performance of indigenous buffalo and need to account for these effects to select buffalo for its genetic merit.